2017
DOI: 10.1136/gutjnl-2016-311892
|View full text |Cite
|
Sign up to set email alerts
|

Are random biopsies still useful for the detection of neoplasia in patients with IBD undergoing surveillance colonoscopy with chromoendoscopy?

Abstract: IRB 001508, Paris 7 University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
95
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 35 publications
3
95
0
7
Order By: Relevance
“…In the SCENIC meta-analysis, eight studies were identified used DCE compared with WLE alone and revealed a significantly greater proportion of patients with dysplasia by using DCE (relative risk (RR)=1.8 (95%CI 1.2 to 2.6) and absolute risk increase of 6% (95% CI 3% to 9%)) 4 35 37–40. Based on a real-life study, random biopsies should still be considered in association with DCE in patients with IBD with a personal history of neoplasia, concomitant PSC or a tubular colon during colonoscopy 41. In SCENIC consensus unanimous agreement could not be reached on this question, although 80% of the panellists favoured targeted biopsies only.…”
Section: Applications Of New Technologies That Are Available In Ibdmentioning
confidence: 99%
“…In the SCENIC meta-analysis, eight studies were identified used DCE compared with WLE alone and revealed a significantly greater proportion of patients with dysplasia by using DCE (relative risk (RR)=1.8 (95%CI 1.2 to 2.6) and absolute risk increase of 6% (95% CI 3% to 9%)) 4 35 37–40. Based on a real-life study, random biopsies should still be considered in association with DCE in patients with IBD with a personal history of neoplasia, concomitant PSC or a tubular colon during colonoscopy 41. In SCENIC consensus unanimous agreement could not be reached on this question, although 80% of the panellists favoured targeted biopsies only.…”
Section: Applications Of New Technologies That Are Available In Ibdmentioning
confidence: 99%
“…Cancer mortality rates were estimated from the National Cancer Intelligence Network Web site, which reports 5-year survival for Dukes stages A/B/C/D. 12 Cancers were assumed to be split evenly across Dukes A and B, and so the mean of the rates for Dukes A and B was used.…”
Section: Derivation Of Transition Probabilitiesmentioning
confidence: 99%
“…8,10,11 Although the use of chromoendoscopy may reduce the rate of endoscopically invisible dysplasia, dysplasia detected by random biopsies can still occur at an appreciable rate (12.8% of all dysplasia detected perpatient) in community-based studies of chromoendoscopy. 12 Several factors must be evaluated in the decision-making process: estimates of the risk of developing a more advanced lesion or CRC after a finding of endoscopically invisible LGD vary, the patient may have undiagnosed concurrent CRC, and the risk associated with surgery depends on both age and comorbidities. Two meta-analyses have considered the risk of developing cancer after a finding of endoscopically invisible dysplasia.…”
mentioning
confidence: 99%
“…In a prospective study of 1000 patients with IBD undergoing surveillance in France, Moussata et al 40 evaluated chromoendoscopy with random biopsies and demonstrated that chromoendoscopy with targeted biopsies detected the majority of patients with dysplasia, and only 15% of patients with neoplasia were identified from random biopsies. Detection of neoplasia in random biopsy was associated with a personal history of neoplasia, tubular appearing colon, and presence of primary sclerosing cholangitis.…”
Section: Random Versus Targeted Biopsiesmentioning
confidence: 99%